2013
DOI: 10.1161/circresaha.113.301075
|View full text |Cite
|
Sign up to set email alerts
|

C3orf58 , a Novel Paracrine Protein, Stimulates Cardiomyocyte Cell-Cycle Progression Through the PI3K–AKT–CDK7 Pathway

Abstract: Rational The regenerative capacity of the heart is markedly diminished shortly after birth coinciding with overall withdrawal of cardiomyocytes from cell cycle. Consequently, the adult mammalian heart has limited capacity to regenerate after injury. The discovery of factors that can induce cardiomyocyte proliferation is therefore of high interest and has been the focus of extensive investigation over the past years. Objective We have recently identified C3orf58 as a novel Hypoxia and Akt induced Stem cell Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 31 publications
4
54
0
Order By: Relevance
“…ExPASy ProtParam online analysis showed that the LOC339524 protein instability index was so large that it could be classified as an unstable protein, suggesting that the protein is active and important. Transmembrane prediction software indicated that at residues 47-68, the protein may have a transmembrane helix, which is consistent with the results reported by Ota et al (2004), suggesting that the protein is a single transmembrane protein without a putative signal peptide, just like hypoxia and Akt-induced stem cell factor (HASF) (Beigi et al, 2013). Further analysis showed that the functional domain of the LOC339524 protein is located at residues 138-236, a region that is likely to induce and regulate cytokine production (Boissanet al, 2014;Turnquistet al, 2014), thereby regulating the immune system.…”
Section: Discussionsupporting
confidence: 87%
“…ExPASy ProtParam online analysis showed that the LOC339524 protein instability index was so large that it could be classified as an unstable protein, suggesting that the protein is active and important. Transmembrane prediction software indicated that at residues 47-68, the protein may have a transmembrane helix, which is consistent with the results reported by Ota et al (2004), suggesting that the protein is a single transmembrane protein without a putative signal peptide, just like hypoxia and Akt-induced stem cell factor (HASF) (Beigi et al, 2013). Further analysis showed that the functional domain of the LOC339524 protein is located at residues 138-236, a region that is likely to induce and regulate cytokine production (Boissanet al, 2014;Turnquistet al, 2014), thereby regulating the immune system.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, evidence of cytokinesis was observed in a murine model 73 . The proliferative effects of HASF were found to be mediated by PI3K and the cell-cycle regulator cyclin-dependent kinase 7 (CDK7) 73 . We are currently investigating in more detail the molecular pathways by which HASF promotes cardiomyocyte proliferation.…”
Section: Effects Of the Paracrine Factorsmentioning
confidence: 96%
“…As noted in a recent editorial HASF has a number of novel features as a cytoprotective factor 136 . Over-expression of PKCε promotes cardiac hypertrophy 137 , whereas that of HASF does not 73 . Moreover, pharmacological inhibition of PKCε did not affect HASF mediated activation of Akt and it is curious feature of HASF that high levels of Akt activity are not important for the cytoprotective effects of this paracrine factor 136 .…”
Section: Emerging Concepts In Paracrine Mechanisms: Temporal and Spatmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we successfully used this model to identify Meis1, one of the key regulators of neonatal cardiac regeneration, and report that Meis1 inhibits cardiomyocyte proliferation through transcriptional activation of CDKIs p15, p16, and p21 . Meis1 knockout 9 (pH3 + CMs, Aurora B + CMs) GSK-3 inhibition (BIO) 5 (pH3 + CMs) (Tseng et al, 2006) Foxo1 dominant negative 2.5 (pH3 + CMs) (Evans-Anderson et al, 2008) miR-133a knockout 2.5 (pH3 + CMs) (Liu et al, 2008) Jumonji knockout 2.2 (pH3 + CMs) (Jung et al, 2005) p27 KIP1 knockout 2-3 (troponin I + CMs) (Poolman et al, 1999) Constitutively active ERBB2 >12 (Ki67 + CMs, pH3 + CMs, Aurora B+ CMs) (D'Uva et al, 2015) Nrg1 (or FGF1, periostin) treatment >4 (BrdU + CMs, Aurora B + CMs, pH3 + CMs,) (Bersell et al, 2009) Activated Yap1 >7 (Ki67 + CMs, pH3 + CMs, Aurora B+ CMs) (von Gise et al, 2012) Salv knockout >4 (pH3 + CMs) (Heallen et al, 2011) IL13 (or IL3, CTGF, Nrg1) treatment >1.5 (3H Thymidine CMs, Ki67 + CMs, BrdU + CMs) Oncostatin M treatment >2 (EdU + CMs) (Kubin et al, 2011) TWEAK treatment 6.2 (BrdU + CMs) (Novoyatleva et al, 2010) C3orf58 treatment >2 (Ki67 + CMs, BrdU + CMs, Aurora B + CMs) (Beigi et al, 2013) Periostin treatment >5 (BrdU + CMs, pH3 + CMs, Aurora B+ CMs) (Kühn et al, 2007) FGF10 treatment 2 (Ki67 + CMs, pH3 + CMs,) (Rochais et al, 2014) Cyclin D2 overexpression >5 (MHC-nLAC + CMs) (Pasumarthi et al, 2005) Cyclin B1-CDC2 or cyclin a2 overexpression >1.4 (CMs) (Bicknell et al, 2004) (Cheng et al, 2007) Activated notch >7 (Ki67 + CMs, BrdU + CMs, Aurora B + CMs) (Campa et al, 2008) c-myc or E1A overexpression 2 (CMs) (Jackson et al, 1990) (Liu and Kitsis, 1996) CM: cardiomyocytes.…”
Section: Kip2mentioning
confidence: 99%